Drawings of traditional dress - Ahmad H.Osman, Rahmah; Ahmad Nadri, Muhammad Nabil (2021)
Drawings of traditional dress worn by the Malay rulers of Malaysia and sultans of Oman as proof of influence between the cultures of Omani and Malay.